Generalised lymphangiectasia: pulmonary presentation in an adult. Issue 7 (July 1996) - White, J. E.; Veale, D.; Fishwick, D.; Mitchell, L.; Corris, P. A.
Abstract : A 25 year old man presented with dyspnoea and was found to have generalised, but predominantly pulmonary, lymphangiectasis without gastrointestinal symptoms. This is an unusual presentation of a disorder previously diagnosed only in childhood.